2017
DOI: 10.1021/acs.nanolett.7b03756
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Tumor-Associated Macrophages To Reverse EGFRT790M Resistance by Dual-Targeting Codelivery of Gefitinib/Vorinostat

Abstract: Gefitinib is a first-line therapy in the EGFR-mutated nonsmall cell lung cancer (NSCLC). However, the development of drug resistance is almost unavoidable, thus leading to an unsustainable regimen. EGFR mutation is the major cause responsible for the molecular-targeting therapy failure in NSCLC. Although the recently approved osimertinib is effective for the EGFR-positive NSCLC, the osimertinib-resistant EGFR mutation is rapidly developed, too. In this study, we proposed a tumor-associated macrophage (TAM) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 22 publications
0
81
0
Order By: Relevance
“…Huang and co‐workers designed a trastumab‐modified mannosylated liposomal formulation loading vorinostat and gefitinib to target the mannose receptor overexpressed TAMs and cancer cells in tumor ( Figure ). [ 55 ] They found that the dual targeting system is able to repolarize TAMs from protumor M2 phenotype toward M1 phenotypes and cause elevated ROS level in cancer cells to resensitize EGFR T790M –positive cells to gefitinib, thereby reversing the EGFR T790M resistance of gefitinib in NSCLC. Upon this treatment, the percentage of CD80 + macrophages (M1 phenotype) in tumor was around 22–26% but that of CD206 + macrophages (M2 phenotype) was less than 5%, indicating the superiority of this dual targeting nanosystem in repolarizing TAMs toward M1 phenotypes.…”
Section: Nanomedicine Mediated Tams Targeting To Promote Their Re‐edumentioning
confidence: 99%
“…Huang and co‐workers designed a trastumab‐modified mannosylated liposomal formulation loading vorinostat and gefitinib to target the mannose receptor overexpressed TAMs and cancer cells in tumor ( Figure ). [ 55 ] They found that the dual targeting system is able to repolarize TAMs from protumor M2 phenotype toward M1 phenotypes and cause elevated ROS level in cancer cells to resensitize EGFR T790M –positive cells to gefitinib, thereby reversing the EGFR T790M resistance of gefitinib in NSCLC. Upon this treatment, the percentage of CD80 + macrophages (M1 phenotype) in tumor was around 22–26% but that of CD206 + macrophages (M2 phenotype) was less than 5%, indicating the superiority of this dual targeting nanosystem in repolarizing TAMs toward M1 phenotypes.…”
Section: Nanomedicine Mediated Tams Targeting To Promote Their Re‐edumentioning
confidence: 99%
“…Adapted with permission from ref. [60]. Copyright (2018) American Chemical Society (neoantigens) of tumor cells to achieve improved clinical performance.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In spite of above‐mentioned limitations, owing to the abundance of TAMs in tumor tissue and considerable immunological impacts on TME, TAM‐targeted therapies are universally applicable regardless of the cancer type, contributing to enhanced tumoricidal functions of T cells and NK cells. Additionally, there are various reported polymeric nanomedicines to deplete TAMs or repolarize TAMs to M1‐like macrophages by delivering colony‐stimulating factor (CSF)‐1R inhibitor, macrophage inhibitor, TLR agonists, low molecular weight of HA, ligands for C‐type lectin receptors, inflammatory cytokines such as IL‐2, iron oxide nanoparticles, and a histone deacetylase inhibitor …”
Section: Application Of Polymeric Nanomedicine To Cancer Immunotherapymentioning
confidence: 99%